Life in the city – example Szombathely - Zsolt Kocsis (Journal for Geography, 2012)
This article deals with culture as an important part of urban life, which is influenced by many factors (including history, society, economy, environment), but which itself influences our quality of life. Although cultural institutions are accessible to all, there is a lack of local opportunities for individual neighbourhoods to enjoy, create and build community through culture. The quality of life of the inhabitants is also affected by where they live. This draws attention to the urban structure, which is a historical product, but also a framework and image for our lives.